Search for charged Higgs bosons produced in association with a top quark and decaying via H± → [tau][nu] using pp collision data recorded at √s = 13 TeV by the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Baas, Alessandra Edda; Brandt, Oleg; Djuvsland, Julia Isabell; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Geisler, Manuel Patrice; Giulini, Maddalena; Hanke, Paul; Jongmanns, Jan; et al. (Physics letters, 2016)
Charged Higgs bosons produced in association with a single top quark and decaying via H±→τν are searched for with the ATLAS experiment at the LHC, using proton-proton collision data at s=13 TeV corresponding to an integrated luminosity of 3.2 fb−1. The final state is characterised by the presence of a hadronic τ decay and missing transverse momentum, as well as a hadronically decaying top quark, resulting in the absence of high-transverse-momentum electrons and muons. The data are found to be consistent with the expected background from Standard Model processes. A statistical analysis leads to 95% confidence-level upper limits on the production cross section times branching fraction, σ(pp→[b]tH±)×BR(H±→τν), between 1.9 pb and 15 fb, for charged Higgs boson masses ranging from 200 to 2000 GeV. The exclusion limits for this search surpass those obtained with the proton-proton collision data recorded at s=8 TeV.